2019
DOI: 10.1016/j.heliyon.2019.e02071
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated and gamma-irradiated waste expanded polystyrene with iron oxide nanoparticles, for removal of indigo carmine dye in textile wastewater

Abstract: In this work, waste expanded polystyrene (WEPS) was irradiated with gamma rays, ranging doses from 100 kGy to 1,000 kGy. After irradiation, the WEPS had decrease on its glass transition temperature (Tg), as consequence of the scissions of its polymer chains. Then, the irradiated WEPS was sulfonated, and its degree of sulfonation (DS) was measured. The highest DS value, 46.6%, was obtained for an irradiation dose of 200 kGy. The sulfonated and irradiated polystyrene (denominated as iS-WEPS), was used as a suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 39 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The fact that the use of more H 2 O 2 than needed produces the hydroperoxyl radical (OOH•), which has a lower oxidation capacity, and this reduces the production rate of HO radicals (Abedinzadeh et al, 2018;Brink et al, 2017). When this study is compared with the previous studies (De Le on-Condés et al, 2019;GilPavas et al, 2017), it is observed that there are differences in removal rates. The main reason of difference in the removal rates is thought to be due to the application of the PFOP directly to the raw textile wastewater in this study.…”
Section: Effect Of the H 2 O 2 Dose On The Pfopmentioning
confidence: 77%
“…The fact that the use of more H 2 O 2 than needed produces the hydroperoxyl radical (OOH•), which has a lower oxidation capacity, and this reduces the production rate of HO radicals (Abedinzadeh et al, 2018;Brink et al, 2017). When this study is compared with the previous studies (De Le on-Condés et al, 2019;GilPavas et al, 2017), it is observed that there are differences in removal rates. The main reason of difference in the removal rates is thought to be due to the application of the PFOP directly to the raw textile wastewater in this study.…”
Section: Effect Of the H 2 O 2 Dose On The Pfopmentioning
confidence: 77%
“…When this study is compared with previous studies performed on COD, SS, and color removal using the PFOP, the findings, which are about the process mechanism, seem to be similar notwithstanding the discrepancies in removal rates. [ 79,80 ] The main difference in removal rates, is thought to have been due to the direct application of the PFOP to the textile wastewater in this study.…”
Section: Resultsmentioning
confidence: 94%
“…The dye concentration in textile wastewater can reach 64.6 mg/L [ 38 ]. Then, the MO and IC equilibrium elimination experiment was realized in a glass vial with a capacity of 25 mL that holds 25 mL of dye solutions at various concentrations (7.5, 15, 30, 50, 75, and 100 mg/L) and 10 mg of nano-sorbent, which were stirred for 1440 min.…”
Section: Experimental Methodsmentioning
confidence: 99%